Analysis of Effect of Different Steps of Vitrification Protocol for Cryopreservation in Ethylene Glycol-Sucrose Medium on 2-Cell Murine Embryo Viability - Smolyaninova, Ye. I.; Pishko, O. V.; Lisina, E. G.; Kolesnikova, A. A.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2007)
The effect of different stages of vitrification protocol for cryopreservation with ethylene glycol-sucrose medium on morphological integrity and viability of 2-cell murine embryos has been studied. This procedure was shown as enabling to preserve viable more than 70% embryos. The stages of exposure in freezing medium and freeze-thawing are mostly responsible for embryo cryoinjury. Basing on the literature reports and own data the role of osmotic and mechanical factors in cell injury at the rapid freezing stages is discussed.